Application of Polymer Materials in Pavement Design - Jiang, Wei; Liu, Quantao; Norambuena-Contreras, Jose; Huang, Yue (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue comprises 17 research articles and 2 review articles, covering studies on both individual and composite polymer modifications. Topics include high-content polymer-modified bitumen, epoxy resin adhesives, SBS-modified bitumen, PE-modified bitumen, crumb-rubber-modified bitumen, and biopolymeric capsules and bitumen rejuvenators.